The relationship of Public Service Motivation on job satisfaction - Kelle Dos Santos Carvalho; Jefferson Lopes La Falce; Ernst Verwaal; Ludmila Vasconcelos Machado Guimarães (Gestão & Regionalidade, 2024)
The objective of this study is to evaluate the influence of the Public Service Motivation on job satisfaction. A Structural Equation’s Modeling was carried out in a Brazilian public university with 7,640 public servants. This study can be considered as a replication. The model that was tested showed that the relationship between the PSM and job satisfaction is positive in the Brazilian context. The results showed that satisfaction is a PSM dependent variable and that the model can be used in mapping the importance that an individual give not only with the relationship between the PSM and job satisfaction but also with each dimension from each construct directing assertively implement Human Resources policies.